Legal Liability of Bhukti Praja Sewakadarma Regional Housing for Vehicle Loss - Ningrat, Ni Nyoman Tara; Kurniawan, I Gede Agus (TATOHI: Jurnal Ilmu Hukum, 2025)
Introduction: The issue of vehicle loss in paid parking areas has frequently led to disputes between consumers and parking operators in Indonesia. In practice, parking operators often attempt to avoid liability by including exemption clauses on parking tickets, thereby creating legal uncertainty for consumers. This situation becomes particularly significant when examined in relation to the role of the Regional Public Company (Perusahaan Umum Daerah / Perumda) Bhukti Praja Sewakadarma, which manages parking facilities in Denpasar City as part of its public service function. This study seeks to examine the legal framework governing the liability of parking operators for vehicle loss under Indonesian legislation and to analyze the scope and limits of Perumda Bhukti Praja Sewakadarma’s legal responsibility within the framework of positive law.Purposes of the Research: The purpose of this research is to analyze the legal standing of parking service users vis-à-vis parking operators and to determine the form of liability that may be imposed on Perumda Bhukti Praja Sewakadarma in the event of vehicle loss.Methods of the Research: The research employs normative legal methods with statutory, conceptual, and case approaches, supported by descriptive qualitative analysis.Findings of the Research: The findings indicate that parking operators, including Perumda Bhukti Praja Sewakadarma, bear strict liability in protecting consumers against losses arising from vehicle theft or disappearance. Jurisprudence, particularly the Central Jakarta District Court Decision Number: 551/Pdt.G/2000/PN Jkt.Pst, confirms that exemption clauses contained in parking tickets are legally invalid. The originality of this research lies in its emphasis on delineating the scope of liability of Perumda as a regional public company, demonstrating the integration of public service principles with consumer protection in the context of parking management.